Teaching braille line tracking using stimulus fading. Issue 3 (14th May 2014) - Scheithauer, Mindy C.; Tiger, Jeffrey H.
<x xml:space="preserve">Abstract</x> Line tracking is a prerequisite skill for braille literacy that involves moving one's finger horizontally across a line of braille text and identifying when a line ends so the reader may reset his or her finger on the subsequent line. Current procedures for teaching line tracking are incomplete, because they focus on tracking lines with only small gaps between characters. The current study extended previous line‐tracking instruction using stimulus fading to teach tracking across larger gaps. After instruction, all participants showed improvement in line tracking, and 2 of 3 participants met mastery criteria for tracking across extended spaces.